2015
DOI: 10.5056/jnm14095
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-dependent Mesenteric Afferent Activation by Mucosal Supernatant From Different Bowel Segments of Guinea Pigs With Post-infectious Irritable Bowel Syndrome

Abstract: Background/Aims Mesenteric afferent nerves (MANs) play a pivotal role in the visceral-nociceptive perception. Inappropriate activation of MANs may be involved in the pathogenesis of post-infectious irritable bowel syndrome (PI-IBS). However, the underlying mechanisms remain unclear. We assessed the effects of mucosal mediators from different bowel segments of guinea pigs with PI-IBS on MAN firing and the role of mast cells. Methods PI-IBS was induced in guinea pigs by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Additionally, the increase in contractions was mediated through activation of purinergic P2X receptors (cation‐permeable ligand‐gated ion channels that open in response to the binding of extracellular adenosine 5'‐triphosphate: ATP), prostanoid receptors, and capsaicin or vanilloid receptors 1 (TRPV1), but not serotonin, histamine, or tachykinin. Exaggerated physiological responses were observed when supernatants of mucosal biopsies were applied to in vitro cell‐systems, in tissues from laboratory animals or humans, or in vivo in animal models; many of these changes were attributable to mediators primarily originating from mast cells (histamine, tryptase, serotonin). All of these findings support the role of mast cell activation in the intestinal dysmotility that has been observed in IBS .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the increase in contractions was mediated through activation of purinergic P2X receptors (cation‐permeable ligand‐gated ion channels that open in response to the binding of extracellular adenosine 5'‐triphosphate: ATP), prostanoid receptors, and capsaicin or vanilloid receptors 1 (TRPV1), but not serotonin, histamine, or tachykinin. Exaggerated physiological responses were observed when supernatants of mucosal biopsies were applied to in vitro cell‐systems, in tissues from laboratory animals or humans, or in vivo in animal models; many of these changes were attributable to mediators primarily originating from mast cells (histamine, tryptase, serotonin). All of these findings support the role of mast cell activation in the intestinal dysmotility that has been observed in IBS .…”
Section: Discussionmentioning
confidence: 99%
“…11,13 The density of MCs in both the small and large bowel may be increased in patients with IBS, but the results are somewhat inconsistent. Some studies demonstrated the number of MCs or the area of mucosa occupied by MCs was increased in IBS patients, 5 moreover, it varies in different genders, 15 in distinct bowel segments 16 and in subgroups of IBS with higher MCs counts in diarrhea-predominant IBS (D-IBS) patients than constipationpredominant IBS (C-IBS) patients. 17,18 However, others suggested there was no significant change in MCs density in IBS.…”
Section: Mast Cells and Irritable Bowel Syndrome: The Presentmentioning
confidence: 99%
“…12,27 Additionally, functional gastrointestinal disorders following acute infectious gastroenteritis not only include PI-IBS, but also post-infectious dyspepsia. 18,28,29 The final symptom complex depends on the interaction between local mucosal injury and central factors including adverse life events, personality, and external stressors.…”
Section: Discussionmentioning
confidence: 99%